Fact-finding and risk factor analysis of chemotherapy-induced nausea and vomiting in children with solid tumors: a prospective observational study - Miaomiao Shao; Ying Li; Jing Qin; Yuchen Zhou; Yixin Sun; Peiyi Yang; Xisi Wang; Cheng Huang; Yan Su; Wen Zhao (BMC Pediatrics)
Abstract Objective The aim of the study was to describe the control of acute chemotherapy-induced nausea and vomiting (CINV) in children with solid tumors receiving highly emetogenic chemotherapy (HEC) at our center. Additionally, the study aimed to explore the risk factors for chemotherapy-induced vomiting (CIV) with the ultimate goal of enhancing CINV management for children. Methods Children aged 1–18 years with solid tumors treated with HEC were enrolled. A structured diary was used to record CINV data, and the pediatric nausea assessment tool (PeNAT) was employed to assess the degree of nausea. The primary outcome was achieving complete CIV control in the acute phase for all children, and secondary outcomes included the control of acute phase CINV, CIV, and chemotherapy-induced nausea (CIN) in children aged ≥ 4 years. Data on children were prospectively collected, and univariate and multivariate logistic regression was used to explore risk factors for complete CIV control. Results A total of 181 children were included, with 52.5% (95/181) experiencing acute phase complete CIV control. Eighty-six children aged ≥ 4 years could be evaluated for acute phase CINV control, and complete CINV control was achieved in 27.9% (24/86), with CIV, CIN complete control rates were 41.9% (36/86) and 34.9% (30/86), respectively. The results of multivariate logistic regression showed age (< 2 years vs. >6 years: OR = 0.186, 95% CI 0.062 ~ 0.56; 2 ~ 6 years vs. >6 years: OR = 0.322, 95% CI 0.145 ~ 0.715), female (OR = 2.034, 95% CI 1.035 ~ 3.994), duration of chemotherapy block (OR = 1.611, 95%CI 1.039 ~ 2.499), and antiemetic regimen (5-hydroxytryptamine-3 receptor antagonists (5HT3RA) vs. 5HT3RA + dexamethasone: OR = 0.395, 95% CI 0.171 ~ 0.914) were statistically significant in complete CIV control (P < 0.05). Conclusions Children with solid tumors treated with HEC at our center experienced suboptimal control of CINV. Older age, female, and a longer duration of the chemotherapy block were identified as risk factors for complete CIV control. Receipt of 5HT3RA plus dexamethasone had a higher likelihood of acute phase complete CIV control versus 5HT3RA. In the future, individualized management of nausea and vomiting, based on existing CINV guidelines and the unique characteristics of children, will be necessary to reduce the incidence of CINV and improve the quality of life for these children.